Polycondensation in liquid crystalline phases of nonionic surfactants. Kinetics and morphology - Kumaraswamy, Guruswamy; Wadekar, M. N.; Agrawal, Vikrant V.; Pasricha, R. (Polymer, 2005)
We have investigated acid-catalyzed polycondensation of alkoxysilane monomers in liquid crystalline phases of nonionic CnEm surfactants. The liquid crystalline phase is retained when the monomers polymerize. The high molecular weight molecules formed phase separate from the mesophase and are subsequently organized by it to form micron-sized particles. A variety of particle morphologies are formed by organization of the polymer particles in the mesophase. For condensation of dimethyldimethoxysilane (DMS, with trimethoxysilane, TMS as crosslinker) in hexagonal and lamellar phases, specific reaction conditions, viz. slow condensation kinetics and low crosslink density, give rod-like particles in hexagonal phases and sheet-like structures in lamellar phases. However, when higher acid concentrations are used, the reaction kinetics accelerates and irregular particles form. Irregular particles also form when the fraction of trifunctional crosslinker is increased, and finally complex flower-like structures form for condensation of trimethoxysilane in the hexagonal phase. The particle morphology formed is crucially dependent on the details of the polycondensation rate, crosslinker density and surfactant-monomer/oligomer interactions. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: nonionic; surfactant; templated synthesis

Polymerization in surfactant liquid crystalline phases - Wadekar, M. N.; Pasricha, R.; Gaikwad, A. B.; Kumaraswamy, Guruswamy (Chemistry of Materials, 2005)
We report the formation of cross-linked polysiloxane particles having rodlike and sheetlike morphologies by condensation of monomers in organized liquid crystalline mesophases of nonionic surfactants. The characteristic diffraction pattern obtained from the liquid crystalline surfactant assembly is preserved during polymer synthesis. The polymer colloids are rodlike when synthesized in a hexagonal mesophase and are sheetlike when synthesized in a lamellar mesophase. Interestingly, the size of the polymer particles is on the order of micrometers, viz. 3 orders of magnitude larger than the characteristic size of the surfactant mesophase. Thus, the polymers phase separate from the liquid crystalline phase during polymerization, and organize to resemble the mesophase geometry. The polymer particles are organized so as to minimize the elastic distortion of the surfactant mesophase after they phase separate. We speculate that the observed particle morphologies are formed due to the slow kinetics of polycondensation under our experimental conditions.

Pathway to copolymer collapse in dilute solution: uniform versus random distribution of comonomers - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2007)
Monte Carlo simulations show that copolymers with uniformly (or periodically) distributed sticky comonomers collapse ``cooperatively,'' abruptly forming a compact intermediate comprising a monomer shell surrounding a core of the aggregated comonomers. In comparison, random copolymers collapse through a relatively less-compact intermediate comprising a comonomer core surrounded by a fluffy monomer shell that densifies over a wide temperature range. This difference between the collapse pathways for random and uniform copolymers persists to higher chain lengths, where uniform copolymers tend to form multiple comonomer cores. In this paper, we describe the formation of such an intermediate state, and the subsequent collapse, by recognizing that these arise from the expected balance between comonomer aggregation enthalpy and loop formation entropy dictated by the chain microstructure. (c) 2007 American Institute of Physics.

Polymer crystallization in the presence of ``sticky'' additives - Dasmahapatra, Ashok Kumar; Nanavati, Hemant; Kumaraswamy, Guruswamy (Journal of Chemical Physics, 2009)
The effect of ``sticky'' additives (viz., those that have attractive interactions with the polymer) on polymer crystallization, has been investigated by dynamic Monte Carlo (DMC) simulations. Additive-polymer attractive interactions result in a slowing down of the polymer chain diffusivity in the melt state. Our results show that with increasing additive stickiness, polymer crystallinity decreases monotonically, and thinner crystallites form, viz., crystallization is inhibited by the presence of sticky additives. Unusually, the observed ``specific heat'' peak at the phase transition shows nonmonotonic behavior with additive stickiness, and exhibits a maximum for intermediate values of additive stickiness. While the origins of this unexpected behavior are not clear, we show that it correlates with a large interchange between crystalline and amorphous states of the monomers, in the vicinity of the additives. At this intermediate additive stickiness, we also find that crystallization follows a qualitatively different route-crystallinity shows a non-Avrami-like evolution, unlike the case at low or high additive stickiness.
Keywords: Additives; amorphous state; crystallisation; crystallites; Diffusion; Monte Carlo methods; polymer melts

Phase separation of DMDBS from PP: effect of polymer molecular weight and tacticity - Sreenivas, K.; Basargekar, Rajeev; Kumaraswamy, Guruswamy (Macromolecules, 2011)
We report an unexpected dependence of DMDBS phase separation temperature on the molecular weight of the matrix isotactic polypropylene (iPP). DMDBS crystallizes out at lower temperatures for iPP with decreasing molecular weight (and correspondingly lower tacticity). All the iPPs in our study are reasonably high molecular weight samples and there is no molecular weight dependence of their solubility parameter. Therefore, the decrease in DMDBS phase separation temperature for lower molecular weights cannot be rationalized using thermodynamic arguments. This molecular weight dependence appears to be unique to isotactic polypropylene and is not observed for either syndiotactic polypropylene or for random copolymers of isotactic polypropylene containing ethylene comonomer.

Phase behaviour of the ternary system: monoolein-water-branched polyethylenimine - Kumar, Manoj; Kumaraswamy, Guruswamy (Soft Matter, 2015)
Addition of a branched polymer, polyethyleneimine, significantly alters the organization of a glycerol monooleate (GMO) lipid-water system. We present detailed data over a wide range of compositions (water content from 10 to 40%, relative to GMO and PEI fractions from 0 to 4%) and temperatures (25-80 degrees C). The PEI molecular weight effects are examined using polymers over a range from 0.8 to 25 kDa. Addition of PEI induces the formation of higher curvature reverse phases. In particular, PEI induces the formation of the Fd3m phase: a discontinuous phase comprising reverse micelles of two different sizes stacked in a cubic AB(2) crystal. The formation of the Fd3m phase at room temperature, upon addition of polar, water soluble PEI is unusual, since such phases typically are formed only upon addition of apolar oils. The largest stability window for the Fd3m phase is observed for PEI with a molecular weight = 2 kDa. We discuss how PEI influences the formation and stability of high curvature phases.

Preparation of macroporous scaffolds with holes in pore walls and pressure driven flows through them - Chatterjee, Soumyajyoti; Potdar, Aditi; Kuhn, Simon; Kumaraswamy, Guruswamy (RSC Advances, 2018)
Controlling the pore architecture in macroporous scaffolds has important implications for their use as reactor packings and as catalyst supports. We report the preparation of a macroporous structure, where the pore walls are perforated by holes. These materials are prepared by modification of the ice-templating protocol developed in our group. We freeze a dispersion of colloidal silica, polymer and cross-linker in a water/acetonitrile medium and allow crosslinking to proceed in the frozen state. The presence of a small fraction of acetonitrile (varying between 1.6% to 6.4%) results in the formation of holes in the pore walls. Increasing the acetonitrile concentration changes the pore size distribution, and produces smaller pores on average. This also results in an increasing fraction of the wall area being covered by small pores, of the order of a few microns in size. Perforation of the walls by pores does not change the overall porosity or modulus of the scaffolds. However, the introduction of pores leads to a drastic reduction in the pressure drop required to pump liquid through the scaffolds. The observed residence time distribution (RTD) in the scaffolds is represented by two plug flow reactors (PFRs) in parallel. The RTD results indicate that increasing the hole fraction in the pore walls results in increased channelling which explains the aforementioned decreased pressure drop during pressure driven flow.

Process-induced microstructure in viscose and lyocell regenerated cellulose fibers revealed by SAXS and SEM of acid-etched samples - Sharma, Aakash; Wankhede, Parnashri; Samant, Roopali; Nagarkar, Shailesh; Thakre, Shirish; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2021)
Regenerated cellulose fibers represent an important class of bioderived commercial fibers. The traditional viscose process requires the use of environmentally harmful carbon disulfide solvent to produce fibers. Lyocell fibers, produced using a more sustainable recent process, exhibit differences in properties from viscose. These differences arise from their semicrystalline microstructure, formed during fiber spinning. It is widely believed that regenerated cellulose fibers predominantly form fringed fibrillar crystals. We optimize acid etching, followed by SEM as an experimental tool to visualize this fibrillar structure. Acid etching provides sufficient topological contrast to directly visualize similar to O(10 nm) fibrils using field-emission scanning electron microscopy (SEM). We combine SEM with small-angle X-ray scattering (SAXS) to reveal other microstructural details. We observe a Bragg peak, indicating the coexistence of stacked lamellar structure with crystalline fibrils for viscose fibers, but not for lyocell. Viscose and lyocell fibers are characterized by partially oriented semicrystalline microstructure. We present a methodology to calculate the Lorentz correction for such microstructure and employ this to analyze the lamellar scattering from viscose fibers using a 1D correlation function approach. We characterize the lamellar microstructure after swelling viscose fibers with water and observe expansion of the Bragg spacing due to water absorption in the amorphous regions. Our data suggest that the water-induced plasticization of amorphous regions is inhomogeneous. Lamellar stacks that are more misoriented from the fiber direction exhibit lower swelling than those along the fiber direction. The experimental methods described in this work reveal interesting details of semicrystalline microstructure in regenerated cellulose fibers, with important implications for the mechanical response of dry and wet fibers. The methods developed here might find use in investigations of other polymer fibers as well.
Keywords: acid etching; crystalline lamellae; fibers; fibrils; Lorentz correction; Regenerated cellulose; SAXS

Polyethylene-grafted sheet-like silsesquioxane nanocomposites with unprecedented adhesion to polar substrates - Sharma, Vivek; Paulbudhe, Uday; Bachhar, Nirmalya; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2023)
Polyethylene is a highly apolar polymer with very pooradhesionto most substrates, necessitating the use of tie layers. Therefore,the synthesis of functional polyethylene is a long-standing challengein catalytic ethylene polymerization. Here, we report the preparationof a nanocomposite comprising polyethylene covalently grafted ontosheet-like silsesquioxanes, with unprecedented adhesion to metal andglass. A norbornene-grafted, layered Mg-silsesquioxane is treatedwith Grubbs second-generation catalyst (G-II), and the identity ofcovalently tethered G-II is unambiguously ascertained. Covalentlytethered G-II catalyzes the ring opening metathesis polymerizationof cyclooctene to poly(cyclooctene). The resulting poly(cyclooctene)is catalytically hydrogenated to yield polyethylene. This polyethylenenanocomposite exhibited a bonding strength of the order of 100 MPaon stainless steel and aluminum, 10-fold higher than reported forengineered polyethylene copolymers. The nanocomposite exhibits anincrease in the polar component of surface energy, yet remains compatibleand cocrystallizes with a polyethylene matrix.
Keywords: adhesion; clay; Nanocomposite; Polyethylene; silsesquioxane